BrainPhys Neuronal Media Support Physiological Function of Mitochondria in Mouse Primary Neuronal Cultures - Faria-Pereira, Andreia; Temido-Ferreira, Mariana; Morais, Vanessa A. (Frontiers in Molecular Neuroscience, 2022)
In vitro neuronal cultures are extensively used in the field of neurosciences as they represent an accessible experimental tool for neuronal genetic manipulation, time-lapse imaging and drug screening. Optimization of rodent primary neurons cultivation led to the development of defined media that support growth and maintenance of different neuronal types. Recently, a new neuronal medium, BrainPhys, was formulated envisioning the mimicry of brain physiological conditions and suitability for cultured human iPSC-derived neurons and rat primary neurons. However, its advantages in mouse primary neuronal cultures and its effects in neuronal bioenergetics were yet to be demonstrated. In this study, we validated the beneficial use of BrainPhys in mouse primary neuronal cultures by observing that neurons cultures in BrainPhys media showed enhanced ATP levels which increased throughout neuronal maturation, a finding that correlates with higher mitochondrial activity and ATP production at later maturation stages, as well as an increased glycolysis response upon mitochondrial inhibition and an increased mitochondrial fuel flexibility. Taken together, our data demonstrates that BrainPhys medium promotes mitochondrial activity along neuronal maturation of in vitro cultures.